The Relationship Between Sleep and Declarative Memory - Nakşidil Torun Yazıhan; Sinan Yetkin (Türk Uyku Tıbbı Dergisi, 2018)

(untitled)
Sleep is a physiologically active process and the function of cognitive processes is known for a long time. It is also known that sleep has a crucial role in two distinct phases of memory. The first one is the information encoding phase which is prior to the learning process; and the second one is the consolidation phase which is related with the persistency of new information after learning occurs. Consolidation is thought as a function of evolutionarily preserved sleep for many forms of memory. The aim of this review is to get together the main study findings which investigating the relationship between the micro and macro structures of sleep and declarative memory processes. Firstly, definition of sleep is given, and then the specific role of sleep in declarative memory consolidation process is explained. In this context, the projected active system consolidation and synaptic homeostasis hypothesis are explicated. The study results investigating the effects of sleep deprivation on declarative memory and information processing phases are summarized. Finally, the role of sleep spindle and slow wave activity on memory processes, which make up the microstructure of sleep, is discussed.